Do Teachers Have the Requisite Digital and Technology Skills for Online Learning?: The Case of A State University in the Philippines - Legarde, Michael Angelo Aguirre (FKIP Universitas Lampung, 2023)
Do Teachers Have the Requisite Digital and Technology Skills for Online Learning? the Case of A State University in the Philippines. This study was conducted to determine the digital and technological skills of the teachers using the TPACK framework. This study employed a cross-sectional explanatory design to determine the technological competence of 196 teachers in a state university in the Philippines. Results of the study show that the respondents have very high pedagogical and content knowledge. This reflects that the teachers demonstrated mastery of content and well-versed of various methodologies and approaches that they used in their teaching. Further analysis also reveals that those teachers who have a very high level of technological competence also have a high level of technology acceptance. Auxiliary to this, teachers who have high technological competence perceived that using technology was highly acceptable. This strongly suggests that educational institutions should continue to conduct intensive trainings and technical support among teachers to further develop their technological skills so that they will become well-versed in using technological tools which are indispensable during online learning. Keywords: tpack, technological competence, digital competence, online learning.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202319